Evaluation of novel approaches to software engineering : 12th International Conference, ENASE 2017, Porto, Portugal, April 28-29, 2017, Revised selected papers /: 12th International Conference, ENASE 2017, Porto, Portugal, April 28-29, 2017, Revised selected papers. (2018) - Unknown
No abstract available